LAMA PEMAKAIAN ALAT ORTHODONTI CEKAT DENGAN STATUS KEBERSIHAN GIGI DAN MULUT PADA PASIEN YANG BERKUNJUNG KE KLINIK GIGI - Yulisa Dashari; Sri Ediati; Ta’adi Ta’adi (Journal of Oral Health Care, 2014)
The need for care orthodonty lately increasing as moreand more patients are aware of the condition of the teethand teeth orthodonty decided to seek treatment as atherapy that can restore the balance of the structure andfunction of the efficiency of the aesthetic harmony of thepatient . The use of fixed orthodonty can affect oral hygieneand accumulation . During orthodonty treatmentprogresses, the formation of plaque , calculus , and gingivitiswhite spot lesions are things that can not be avoidedespecially when the patient is very bad oral hygiene. Thisresearch aims to determine the correlation between thetime of using fixed orthodonty with dental and oral hygienestatus of the patient . Observational study with cross sectionaldesign . This research is doing in 2013 . The locationof research is at Dental Clinic Ibnu Sina with the timeof using Fixed Orthodonty tools at least 3 months and subjectsof research age between 15th – 45 th years. The studywas conducted by measuring the value of oral hygienescores of patients with a long record OHIS and use oftools orthodonty research subjects . Analyzis datas usethe statistic test bivariat spearman Rho with significancylevel = 0,05. There was no significant correlation betweenduration of use fixed orthodonty with dental and oral hygienestatus, with a significance level of 0.164 was obtained> 0.05. The results showed the use of the old appliancefixed orthodonti the longest was 60 months and thecriteria of Dental and Oral Health Status ( OHIS ) the mostmedium with total 18 persons.